PENERAPAN HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGA JUAL PRODUK DENGAN MENGGUNAKAN METODE FULL COSTING - Suprajitno, Dwi; Suprajitno, Dwi (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2014)
ABSTRACT To determine the production cost using full costing method that focuses on the presentation of the elements of the cost of the main functions of the company. In determining theproduction costinformationis neededbythe company is the production cost information regarding the costof raw materials, labor costs, and factory overhead costs. So the cost of production resulting information is reliable,both for determining the selling price of products as well as forthe calculation of periodic income. If the experience in operating profit, the profit is what will be used by the company to develop and maintain their business. This study aimed to evaluate the application of methods of determining the cost of production isused by the CV. Eternal Source of Light as determining the selling price of its products. And this study provides a step by HPP calculations based on existing data and compare it with HPP used by the company in determining the selling price of the product.